Editorial: The Relevance of Comics and their Screen Adaptations Journal for Religion, Film and Media - Christian Wessely (Journal for Religion, Film and Media, 2017)
Editorial of JRFM 2017, 3/1 : Drawn Stories, Moving Images. Comic Books and their Screen Adaptations